INNOVATIVE TECHNOLOGIES IN EARLY DIAGNOSIS OF PRECANCER AND CANCER DISEASES OF THE CERVIX - Bakhtiyarovna, Isakova Dilnoza; Rafikovna, Farmankulova Yorkinoy (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Background: Cervical cancer (CC) remains a significant oncological challenge, as its early detection and intervention can substantially improve patient outcomes, including overall and recurrence-free survival, enhance quality of life, and reduce treatment costs. Specific Background: The primary etiological factor for cervical cancer is infection with oncogenic genotypes of the human papillomavirus (HPV), which is preventable through effective screening measures. Knowledge Gap: Despite the availability of screening tests, there remains a critical need for advancements in diagnostic technologies to enhance early detection rates and precision in identifying precancerous lesions and invasive cancer. Aims: This study aims to evaluate the impact of innovative technologies on the early diagnosis of precancerous conditions and cervical cancer, focusing on improvements in diagnostic accuracy, early detection, and subsequent patient management. Results: The integration of novel diagnostic technologies, such as advanced HPV testing methods, liquid biopsy techniques, and high-resolution imaging, has demonstrated significant improvements in detecting cervical abnormalities at earlier stages compared to traditional methods. These technologies enhance diagnostic precision and enable more targeted interventions. Novelty: This research highlights recent advancements in diagnostic technologies that offer higher sensitivity and specificity, including the use of biomarkers and novel imaging modalities, which represent a shift towards more personalized and effective cervical cancer screening strategies. Implications: The findings underscore the potential for these innovative technologies to revolutionize cervical cancer screening and diagnosis, ultimately leading to improved patient outcomes, reduced healthcare costs, and more effective management of cervical cancer and its precursors.